Extracellular Vesicles From Gastric Cancer Cells Induce PD-L1 Expression on Neutrophils to Suppress T-Cell Immunity - Shi, Yinghong; Zhang, Jiahui; Mao, Zheying; Jiang, Han; Liu, Wei; Shi, Hui; Ji, Runbi; Xu, Wenrong; Qian, Hui; Zhang, Xu (Frontiers in Oncology, 2020)
Neutrophils are prominent components of solid tumors and exhibit distinct phenotypes in different tumor milieu. We have previously shown that tumor extracellular vesicles (EVs) could induce pro-tumor activation of neutrophils; however, the role of tumor EVs-elicited neutrophils in tumor immunity remains unclear. Herein, we reported that gastric cancer cell-derived EVs (GC-EVs) induced the expression of programmed death-ligand 1 (PD-L1) on neutrophils. GC-EVs transported high mobility group box-1 (HMGB1) to activate signal transducer and activator of transcription 3 (STAT3) and upregulate PD-L1 gene expression in neutrophils. Blocking STAT3 pathway and silencing HMGB1 reversed GC-EVs-induced PD-L1 expression on neutrophils. GC-EVs-elicited neutrophils suppressed T cell proliferation, activation and function in vitro, which could be antagonized by a specific PD-L1 antibody. Furthermore, gastric cancer tissues derived EVs also showed the similar effects. Taken together, our results indicate that EVs from GC microenvironment induce PD-L1 expression on neutrophils to suppress T-cell immunity, which provides a new insight into the pro-tumor roles of neutrophils in gastric cancer and sheds lights on the multifaceted roles of EVs in orchestrating immunosuppressive microenvironment.